ANALYSIS OF THE EFFECT OF SELF ASSEMBLED MONOLAYER (SAM) ON THE ZNO MONOLAYER AS A SELECTIVE GAS SENSOR: DENSITY FUNCTIONAL THEORY STUDY - Fadlan Raihan, Muhammad
The addition of Self-Assembled Monolayer (SAM) to the gas sensor attempts to modify the properties of gas detection to produce a more sensitive and selective sensor. In addition, studies regarding the adsorption properties of ZnO Monolayer as a gas sensor are still needed to determine the potential of this type of material on the topic of detection. This study analyzes the effect of the addition of SAM on ZnO Monolayer on electronic and magnetic properties using the Density Functional Theory (DFT) method to see the relationship with its adsorption performance as a gas sensor. First, the system geometry structure is optimized to produce the most optimum energy, and calculations are carried out on the adsorption energy, band structure, and charge transfer. Furthermore, an analysis of the Total Density of States (TDOS) and Partial Density of States (PDOS) was carried out to find out more about the interaction between the ZnO monolayer, gas molecules, and the effect of SAM on the adsorption system. Based on calculations, after performing geometry optimization, the ZnO Monolayer layer turned into a honeycomb structure similar to graphene, with a bond length between Zn-O of 1.897 Å and a bandgap of 1.83 eV and is a non-magnetic semiconductor material. After adsorption of the ZnO surface with NO2, the gas position at the bridge site was the most optimum, with an adsorption energy of 0.432 eV. The surface structure changes with the bonds between the atoms being slightly distorted downwards. The band structure and DOS curves show hybridization, which indicates a transfer of charge between atoms in ZnO and NO2 and changes in these materials' electronic and magnetic properties. Adsorption of ZnO surface with SO2 also showed that the gas position at the bridge site was the most optimum with an adsorption energy of 0.52 eV. The surface structure changed, the SO2 molecule also dissociated and diffused with the ZnO monolayer surface. Band structure and DOS showed that there is hybridization which indicated charge transfer between the atom of the ZnO and SO2. A significant change occurs in the adsorption system after simulating SAM with the ZnO monolayer toward the gases (NO2 and SO2). The adsorption energy of the surface toward NO2 and SO2 are -5,26 eV and -2,47 eV. This energy indicates that SAM enhances the sensing performance of the ZnO monolayer toward gases and increases its selectivity toward NO2. Furthermore, We analyzed the DOS and Band structure which show that hybridization occurs between atoms in the adsorption system of ZnO/SAM/NO2 and ZnO/SAM/SO2 and also caused the change of the electronic and magnetic properties of this material.